Upaya Pencegahan Kecelakaan Kerja Di Kamar Mesin Pada Kapal MT. Pink Diamond - Musriady Musriady (Celebes Engineering Journal, 2020)
The role of the use of safety equipment is one attempt to prevent or reduce accidents at work. Therefore, it is expected that the entire crew and workers on board always use safety equipment when working in order to avoid things that are not desirable as an accident. This incident happened on MT. Pink Diamond when the writer worked on board. The data sources was obtained directly from the ship where the writer worked. The principal purpose of the writing is to know the efforts the use of safety equipment in engine room to ensure safety on MT. Pink Diamond. Finally, the writer concluded in order to answer the safety in engine room on MT. Pink Diamond that accident happened because of the lack of awareness and discipline of the crew in using safety equipment.